Effect of Single‐Dose, Oral Enzymatic Porcine Placental Extract on Pharmacokinetics of Alcohol and Liver Function in Rats. (11th April 2020) - Kim, Hyun‐Jin; Kim, Semi; Seo, Jin‐Sook; Bae, Gun‐Won; Kim, Keun‐Nam; Kang, Ju‐Seop
Abstract : Background: Human placenta extract (HPE) has been used to treat a number of liver diseases. Porcine placenta is relatively safe and has been reported to have similar immune effects to HPE and used as its alternative. This study evaluates the effect of enzymatic porcine placental extract (EPPE, Uni‐Placenta®) on alcohol pharmacokinetics in rat. Methods: This study was designed to determine the effect of single‐dose EPPE on the pharmacokinetics of alcohol and liver function. Results were based on serum alcohol and acetaldehyde concentrations and activities of hepatic and gastric ADH and ALDH in rats. Results: The hepatic ADH in alcohol group was significantly increased and it may be enzyme‐induction by alcohol. The hepatic ALDH and gastric ADH were not changed, but gastric ALDH was significantly decreased only in the high‐dose EPPE group. In the alcohol pharmacokinetics parameters, the AUC was 44.5 mM∙h in the alcohol group. Otherwise, AUCs of low, middle, high, and silymarin groups were significantly decreased. C max was reached at 1 hour and then gradually decreased to 63% and 43% in the middle and high groups at 3 hours, respectively, and to 92% in the low groups. The pharmacokinetics and serum concentrations of acetaldehyde showed no differences between EPPE groups except the silymarin group. No histologic changes were seen in any group. Conclusions: The single‐dose EPPE (0.5 to 2.5 g/kg) suppressed absorption of alcohol in the gastrointestinal tract. This may be useful in preventing hangover effects and toxicity after drinking alcohol and may also preserve liver health after alcohol ingestion. Abstract : This study was designed to determine the effect of single‐dose EPPE on the pharmacokinetics of alcohol and liver function. In the alcohol pharmacokinetics parameters, the AUC and Cmax were significantly different between the control and other groups. In conclusion, the singledose EPPE suppressed absorption of alcohol in the gastrointestinal tract. Therefore, this may be useful in preventing hangover effects and toxicity after drinking alcohol and may also preserve liver health after alcohol ingestion.